Modern approaches to the correction of the gut microbiota - N. V. Sturov (Медицинский совет, 2021)
The article presents modern data on the formation, structure, functions and possibilities of correction of the gut microbiota. The gut microbiota is a collection of living organisms that inhabit the human intestine and form a complex microecological system that performs many functions. It is known that the composition and state of the gut microbiota is influenced by both environmental factors, such as diet and lifestyle, and the human body, including genetic predisposition. A violation in this system (dysbiosis) can provoke the development of a number of diseases and pathological conditions, in which the correction of the gut microbiota may be a promising therapeutic strategy. The most common methods of correcting dysbiosis are dieting, the use of pro-and prebiotics, and fecal microbiota transplantation. The diet affects the qualitative and quantitative composition and functions of the gut microbiota, the activity of its individual representatives. Probiotics are used to modulate, preserve the gut microbiota in dysbiosis, as well as to prevent its development. Fecal microbiota transplantation is performed by transferring the microbiota from a healthy donor. This method is one of the most effective ways to treat Clostridium difficile infection. This review article also presents the results of fecal microbiota transplantation in patients with inflammatory bowel disease and hepatic encephalopathy. It is shown that after transplantation, there is a rapid change in the composition of the gut microbiota, which becomes similar to the microbiota of a healthy donor. Each of these methods of correction demonstrates a different degree of influence on the gut microbiota, and their therapeutic effectiveness depends on the direct characteristics of the methods used, as well as the specific disease and requires further study.